Analysis of IPS Laboratory Needs in Junior High School - Azharotunnafi, Azharotunnafi; Nabilah, Hafidzoh (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
This research aims to find out the analysis of the laboratory needs of IPS in Mu’allimat NU Gresik through objective conditions, the perceptions of teachers and students of IPS, and the potential development of laboratory IPS at Mu’allimat NU Gresik. Research uses qualitative methods with descriptive approaches. The location of the research was at the educational institute of SM Mu'allimat NU Gresik, East Java. As for the subjects in this study, they are IPS teachers, students, the deputy chief of the field of facilities, and the deputy head of the student field. The data-gathering technique that researchers use is through observations, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion drawing. Verification of the validity of the data in this study uses triangulation of the data. The results of the research showed that Mu’allimat NU Gresik needs an indoor and outdoor IPS laboratory to support students’ learning. However, there are obstacles to the provision of indoor IPS labs in schools. So the use of indoor laboratories is implemented as a digital laboratory. Simulations carried out in indoor IPS laboratories are realized through images presented by digital laboratories.